Hypophosphatemia is an independent risk factor for AKI among hospitalized patients with COVID-19 infection. Issue 1 (1st January 2021) - Chen, Zijin; Gao, Chenni; Yu, Haijin; Lu, Lin; Liu, Jialin; Chen, Wei; Xiang, Xiaogang; Hussain, Hafiz Muhammad Jafar; Lee, Benjamin J.; Li, Chuanlei; Wei, Wenjie; Huang, Yuhan; et al.
Abstract: Background: This study sought to investigate incidence and risk factors for acute kidney injury (AKI) in hospitalized COVID-19. Methods: In this retrospective study, we enrolled 823 COVID-19 patients with at least two evaluations of renal function during hospitalization from four hospitals in Wuhan, China between February 2020 and April 2020. Clinical and laboratory parameters at the time of admission and follow-up data were recorded. Systemic renal tubular dysfunction was evaluated via 24-h urine collections in a subgroup of 55 patients. Results: In total, 823 patients were enrolled (50.5% male) with a mean age of 60.9 ± 14.9 years. AKI occurred in 38 (40.9%) ICU cases but only 6 (0.8%) non-ICU cases. Using forward stepwise Cox regression analysis, we found eight independent risk factors for AKI including decreased platelet level, lower albumin level, lower phosphorus level, higher level of lactate dehydrogenase (LDH), procalcitonin, C-reactive protein (CRP), urea, and prothrombin time (PT) on admission. For every 0.1 mmol/L decreases in serum phosphorus level, patients had a 1.34-fold (95% CI 1.14–1.58) increased risk of AKI. Patients with hypophosphatemia were likely to be older and with lower lymphocyte count, lower serum albumin level, lower uric acid, higher LDH, and higher CRP. Furthermore, serum phosphorus level was positively correlated with phosphate tubular maximum per volume of filtrate (TmP/GFR) (Pearson r  = 0.66, p  < .001) in subgroup analysis, indicating renal phosphate loss via proximal renal tubular dysfunction. Conclusion: The AKI incidence was very low in non-ICU patients as compared to ICU patients. Hypophosphatemia is an independent risk factor for AKI in patients hospitalized for COVID-19 infection.